2-Iodoxybenzoic acid organosulfonates: preparation, X-ray structure and reactivity of new, powerful hypervalent iodine(V) oxidants; Chemical Communications; Vol. 49, iss. 96 - Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Svitich D. Yu. Dmitry Yurjevich; Yoshimura A. Akira; Nemykin V. N.; Zhdankin V. V. Viktor Vladimirovich (2013, 2013)
Title screen